The Relationship of Surface Ozone Pollution with Meteorological Conditions in Determining Episode Periods - Taufik Rizki Ramadhan; Didin Agustian Permadi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Jakarta, the capital city of Indonesia, is located in a tropical region with abundant sunlight and high temperatures year-round. Ozone and particulate matter (PM) are critical parameters causing unhealthy air pollution. Meteorological data were obtained from the NASA Power website. This study aims to explore the relationship between ozone formation and meteorological factors in Jakarta. Ozone air quality data were measured using the Backman model 950A ozone Analyzer, which detects concentrations as low as 0.05 ppm, with measurements taken every 40 seconds. From January to October 2023, ozone concentrations increased during the dry months of May to October, with the highest hourly value recorded at 263 μg/m³. During this period, average temperatures ranged from 27-29°C, rainfall was 0.3-5.6 mm, wind speeds were 3.14-4.64 m/s, wind direction was 92-171 degrees, and air humidity was 74-82%. Significant episodes were identified on (i) May 5-9, (ii) July 12-15, (iii) September 6-7, (iv) September 13-14, (v) September 21-22, and (vi) October 29-30, 2023. Daily, monthly, and seasonal ozone variations aligned with meteorological conditions, showing higher concentrations during the dry months. Further studies, including photochemical modeling, are required to identify dominant factors causing high ozone concentrations during these episodes. Understanding NOx or VOC emission sensitivities is crucial for effective ozone abatement strategies in Jakarta.